Regulation of gene expression is preserved in aging Drosophila melanogaster. - Rogina, B.; Vaupel, J.W.; Partridge, L.; Helfand, S.L. (Current Biology, 1998)
Aging, and the deterioration of biological performance that characterizes it, are routinely assumed to be due to a progressive global loss of homeostasis and a general increase in dysregulation [1-4] . We tested this hypothesis directly by measuring age-specific variability in gene expression. Analysis of the transcriptional activity of six genes in various inbred lines of Drosophila melanogaster unexpectedly failed to show an increase in variability among individuals as they age and die. Although regulation of gene expression is a central feature of life, a global decline in the control of gene expression does not appear to be either a cause or a consequence of the process of aging.